Metamodern Sincerity in Musiienko’s Novel “In Search of Hay for Horses and Lovers: A Diary in a Time of War” - Drozdovskyi, Dmytro (Respectus Philologicus, 2026)
In this article, the author has discussed Viacheslav Musiienko’s novel In Search of Hay for Horses and Lovers: A Diary in a Time of War (2025) as an example of the metamodern narrative. This diary reinforces memories from the initial days and months of the full-scale invasion of Ukraine on February 24, 2022. The narrative is meant to serve as a medium for expressing existential pain and for sharing the narrator’s psycho-emotional feelings. Moreover, this diary genre reinforces precise event documentation, yet the narrator’s reflective approach is a key that offers comparisons with past events and philosophical reflections on the wartime reality and ecology. This results in a distinct narrative voice that eschews excessive embellishment while allowing for existential insights into the “new normality”. It has been stated that this diary effectively chronicles events with broader political implications during wartime, depicting personal experiences with detailed chronology. It analyses the media representation of these events, highlighting humanitarian and anthropocentric intentions. It was found out that these elements illuminate the narrator’s worldview, engaging readers in a search for psychological anchors amidst the chaos of war. It has been outlined that Musiienko’s fiction is ecological and anthropocentric, erasing traditional hierarchies and creating a metamodern narrative. The narrator considers societal entropy linked to chaos. Musiienko’s diary is a model of philosophical fiction that emphasises insights into human and animal experiences – victims of missile attacks. It has been found that this narrative stresses the true tragedy of war while minimising metaphorical constructs, focusing instead on historical storytelling that captures psychological, ethical, ecological, and humanitarian aspects.